Exploring the UWEC Campus Climate Surrounding Disabilities - Beck, Katie; Marx, Amanda; Niquette, Melanie; Prahl, Alison; Risberg, Kellie (My University, 2015)
The purpose of this study was to examine college students' attitudes toward disability and their perceptions of their campus engagement and satisfaction. By assessing students' attitudes toward disability and their perceptions of campus engagement, we hope to gain a better understanding of the current campus climate as it relates to disability and whether or not students with disabilities are indeed at risk of being impacted by disability stigma.
Color poster with text and graphs.
Keywords: Disability stigma; Disabilities; College students; Posters